2006
DOI: 10.1007/s11255-005-4763-3
|View full text |Cite
|
Sign up to set email alerts
|

The significance of p53 and bcl-2 overexpression and other prognostic factors in transitional cell carcinoma of the bladder

Abstract: The aim of this study was to investigate the expression of bcl-2 and p53 oncoproteins in a series of transitional cell bladder carcinomas and its relation to traditional prognostic indicators and patients' survival. Specimens from 59 patients who underwent transurethral resection from March 1992 to February 1997 were included in this study. Tumors were graded based on WHO grades 1-3 and staged according to the 1997 TNM classification. Three patients lost to follow-up were excluded from the analysis. We could n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our results showed that the combined treatment of ginsenoside Rg3 and cisplatin was associated with the reduced level of expression in Bcl-2. Duggan et al showed that the downregulation of Bcl-2 protein enhanced mitomycin C induced apoptotic cell death in bladder cancer (20), although the prognostic significance of those findings was not consistent in the literature (21)(22)(23)(24). Bolenz et al also demonstrated that the addition of Bcl-2 antisense oligodeoxynucleotides enhanced the cytotoxic potential of cisplatin as well as other chemotherapeutic agents such as mitomycin C in transitional carcinoma cell lines (25).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the combined treatment of ginsenoside Rg3 and cisplatin was associated with the reduced level of expression in Bcl-2. Duggan et al showed that the downregulation of Bcl-2 protein enhanced mitomycin C induced apoptotic cell death in bladder cancer (20), although the prognostic significance of those findings was not consistent in the literature (21)(22)(23)(24). Bolenz et al also demonstrated that the addition of Bcl-2 antisense oligodeoxynucleotides enhanced the cytotoxic potential of cisplatin as well as other chemotherapeutic agents such as mitomycin C in transitional carcinoma cell lines (25).…”
Section: Discussionmentioning
confidence: 99%
“…Outside of our panel of biomarkers, there are several other exploratory markers that might be worth further research; these include: p21 [2,12,14,19], Her‐2 [72–75], Bax/bcl‐2 [76–79] and CD40 [80,81]. Epigenetic processes, such as DNA methylation and histone acetylation, also represent important mechanisms in carcinogenesis [4,5].…”
Section: Other Markersmentioning
confidence: 99%
“…This difference might be explained by the hormonal differences between men and women and social habits (tobacco smoking is more common in men). 1,18 In addition to the fact that androgen receptors have a major role in development of cancer, 1,18 which is much more active in men than in women. 1 Statistically, there was no significant correlation between Bcl2 over-expression and sex of the patients.…”
Section: 8mentioning
confidence: 99%